From Blood to Outcome: Inflammatory Biomarkers in Rectal Cancer Surgery at a Romanian Tertiary Hospital - Georgiana Viorica Moise; Catalin Vladut Ionut Feier; Vasile Gaborean; Alaviana Monique Faur; Vladut Iosif Rus; Calin Muntean (Diseases)
Background: Systemic inflammatory markers have emerged as accessible and reproducible tools for oncologic risk stratification, yet their prognostic value in rectal cancer remains incompletely defined, particularly in acute surgical settings. This study aimed to assess six inflammation-based indices—NLR, PLR, MLR, SII, SIRI, and AISI—in relation to tumor stage, recurrence, and outcomes among patients undergoing emergency versus elective resection for rectal cancer. Methods: We retrospectively evaluated 174 patients treated between 2018 and 2024. Pre-treatment blood counts were used to calculate inflammatory indices. Clinical and pathological parameters were correlated with biomarker levels using univariate and multivariate analyses. Results: Pre-treatment inflammation markers were significantly elevated in patients requiring emergency surgery (e.g., NLR: 3.34 vs. 2.4, p = 0.001; PLR: 204.1 vs. 137.8, p < 0.001; SII: 1008 vs. 693, p = 0.007), reflecting advanced tumor biology and immune activation. Notably, these patients also had higher rates of stage IV disease (p = 0.029) and permanent stoma (p = 0.002). Post-treatment, recurrence was paradoxically associated with significantly lower levels of SII (p = 0.021), AISI (p = 0.036), and PLR (p = 0.003), suggesting a potential role for immune exhaustion rather than hyperinflammation in early relapse. Conclusions: Inflammatory indices provide valuable insights into both tumor local invasion and host immune status in rectal cancer. Their integration into perioperative assessment could improve prognostication, particularly in emergency presentations. Post-treatment suppression of these markers may identify patients at high risk for recurrence despite initial curative intent.